ANTESEDEN KINERJA; KOMPETENSI, LINGKUNGAN KERJA NON FISIK DAN DISIPLIN - Adolfitri Lolo Tarukallo; Conchita Valentina Latupapua; Agusthina Risambessy (Jurnal Ilmiah Global Education, 2023)
The purpose of this study was to determine the effect of competence, non-physical work environment, and discipline on employee performance at the Galay Dubu Village Office, Aru Islands Regency. The method in this study uses causal research with a quantitative approach using a questionnaire as a data collection tool. The population in this study were employees who worked at the Galay Dubu Village Office, Aru Islands Regency. The sample size used in this study was 36 respondents. This study used SPSS version 21. Using saturated sampling, the findings in this study indicate that competence, non-physical work environment and discipline have a positive and significant effect on employee performance.